TO THE RISK MANAGEMENT IN LOGISTICS SYSTEMS - Dolia, V. K.; Lezhneva, Ye. I. (Science and Transport Progress, 2008)
The analysis of models of risk representation and estimation as applied to logistic systems at management of processes in delivery chains is conducted.